Kemampuan Penggunaan Ukemibun Pada Mahasiswa Program Studi Pendidikan Bahasa Jepang Tahun Masuk 2020 Universitas Negeri Padang - jefri - sepriadi; Hendri Zalman (Universitas Negeri Padang, 2022)
The background to this study is the undocumented fact that the value of the ability to use ukemibun among students of the 2020 enrollment Japanese Language Education Study at Padang State University. The purpose of this study is to describe the abilities of Ukemibun students of the Japanese language education study program for the 2020 entry year at Padang State University. The type of research used in this study is quantitative research with descriptive methods. The population in this study were 53 students of the Japanese language education study program Class of 2020, Padang State University. The sample in this study amounted to 26 people. The results of this study indicate that students' ability to master ukemibun is at an average score of 6.6 with the qualification of 'Good Enough'. From these results it can be concluded that the aspect of identifying words marked with particles in ukemibun needs to be considered in learning.